2021
DOI: 10.1002/1878-0261.12911
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NKX2‐1‐AS1 promotes tumor progression and angiogenesis via upregulation of SERPINE1 expression and activation of the VEGFR‐2 signaling pathway in gastric cancer

Abstract: Long noncoding RNAs (lncRNAs) can compete with endogenous RNAs to modulate the gene expression and contribute to oncogenesis and tumor metastasis. lncRNA NKX2‐1‐AS1 (NKX2‐1 antisense RNA 1) plays a pivotal role in cancer progression and metastasis; however, the contribution of aberrant expression of NKX2‐1‐AS1 and the mechanism by which it functions as a competing endogenous RNA (ceRNA) in gastric cancer (GC) remains elusive. NKX2‐1‐AS1 expression was detected in paired tumor and nontumor tissues of 178 GC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 41 publications
(41 reference statements)
3
35
1
Order By: Relevance
“…Third, considering that TARBP2 involves in multiple cellular processes, particularly its function in regulating the accuracy of miRNA processing ( 46 ), we aimed to elucidate an epigenetic pathway via miRNAs for the TARBP2-SERPINE1 axis in HCC progression. Our findings suggested that sh- TARBP2 reduced the synthesis of mature miR-145, which have been identified to directly target SERPINE1 in previous reports ( 17 , 47 , 48 ). Next, we validated the relationship between SERPINE1 and miR-145 in HCC using dual luciferase assays and clinical samples.…”
Section: Discussionsupporting
confidence: 78%
“…Third, considering that TARBP2 involves in multiple cellular processes, particularly its function in regulating the accuracy of miRNA processing ( 46 ), we aimed to elucidate an epigenetic pathway via miRNAs for the TARBP2-SERPINE1 axis in HCC progression. Our findings suggested that sh- TARBP2 reduced the synthesis of mature miR-145, which have been identified to directly target SERPINE1 in previous reports ( 17 , 47 , 48 ). Next, we validated the relationship between SERPINE1 and miR-145 in HCC using dual luciferase assays and clinical samples.…”
Section: Discussionsupporting
confidence: 78%
“…Excessive angiogenesis is an essential characteristic of cancer, which account for the tumor proliferation ( Liu et al, 2019 ), invasion ( Zeng et al, 2018 ), chemoresistance ( Marti et al, 2015 ), etc., Emerging evidences have indicated that lncRNAs participate in regulating malignant phenotypes and act as critical clinical biomarkers for diagnosis and prognosis in multiple malignancies ( Yang et al, 2019 ; Zhao et al, 2019 ; Gao et al, 2020 ; Shi et al, 2021 ). Although several angiogenesis-related lncRNAs have been identified in gastric cancers ( Liu H. T. et al, 2020 ; Teng et al, 2021 ), effective anti-angiogenesis strategies in GC are still limited and the underlying mechanisms remain to be further disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of protein expression was conducted referring to the descriptions of issued studies [ 18 , 19 ]. The primary antibodies against collagen I (ab34710, 1:1000), collagen IV (ab7536, 1:1000), HMGA2 (ab207301, 1:1000) and GAPDH (ab181602, 1:3000) were acquired from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%